2001
DOI: 10.1097/00007632-200111150-00020
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Diagonal Fixation in Pedicle Screw Instrumentation

Abstract: The results of this study showed that diagonal transfixation provides more rigid fixation in flexion and extension but less in lateral bending and axial rotation in comparison with horizontal transfixation. Furthermore, greater stresses in the pedicle screws were predicted in the diagonal transfixation model. These limitations of diagonal transfixation should be considered carefully for clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 7 publications
0
31
0
4
Order By: Relevance
“…The calf is the species mainly used in vitro. Tests with pedicle screw systems are counted among these experiments [3,4,6,9,11,17,18]. According to the results of the present study, these experiments reveal the right trends but should not be interpreted quantitatively.…”
Section: Discussionmentioning
confidence: 74%
“…The calf is the species mainly used in vitro. Tests with pedicle screw systems are counted among these experiments [3,4,6,9,11,17,18]. According to the results of the present study, these experiments reveal the right trends but should not be interpreted quantitatively.…”
Section: Discussionmentioning
confidence: 74%
“…The addition of crosslinks is one strategy, and previous studies have shown increased stiffness in lateral bending and axial rotation upon such an addition. 2,17,26 In addition, construct stiffness is also dependent on the grade of facetectomy, 1,29 and the type, size, and orientation of the intervertebral cage. 7,14,25 Tsitsopoulos et al performed a biomechanical analysis on a lumbar interbody fusion technique using cadaveric spines, and concluded that the greater stability of the TLIF construct was due to more anterior placement of the cage and preservation of the contralateral facet joint.…”
Section: Discussionmentioning
confidence: 99%
“…Despite technological advances, implant failures, such as screw bending, breakage, and loosening still occur [2,10,40]. It is well established in the literature that the holding power of the pedicle screw is influenced by bone mineral density [5], geometry of the screw [1,20,[25][26][27] and the screw insertion technique employed by the surgeon [5,14,33,38]. It has been reported that the holding power of the pedicle screw is significantly influenced by the size and technique of the pilot hole [5,7,14,15,33].…”
Section: Introductionmentioning
confidence: 99%